Isolasi dan Uji Aktivitas Selulolitik Bakteri Asal Limbah Bagas - Dewi Chusniasih; Erma Suryanti; Erina Safitri (Institut Pertanian Bogor, 2023)
Bagasse is one of the by-products of granulated sugar industries or processed beverages that become waste in the environment. The bagasse will be overgrown by cellulolytic bacteria that produce cellulase enzymes. This study aims to isolate, characterize, and measure bacterial cellulase activity qualitatively and quantitatively. The research phase included isolation and characterization of bacteria, qualitative cellulase activity test, preparing standard curves and bacterial growth curves, crude extract cellulase production, constructing standard glucose curves, quantitative enzyme activity tests, and data analysis. Six isolates with macroscopic characteristics varied in color, elevation, margins, and colony shape; three bacillus isolates, one short bacillus isolate, and two cocci isolates were obtained. All isolates showed positive test results of amylum, triple sugar iron agar, and catalase; five citrate-positive isolates, and three motile-positive isolates. From the cellulase qualitative test, two bacterial isolates had the highest cellulolytic index, namely AT1 (1.79) and BAW3 (1.72) on 0.5% CMC media. The quantitative cellulase test results of the two selected isolates were 0.01176 U/mL for AT1 and 0.01170 U/mL for BAW3, both of which are still classified as low degradation capabilities. Keywords: cellulase activity, cellulolytic index, Sugarcane waste